Faktor Yang Mempengaruhi Intensi Masyarakat Menjadi Nasabah Bank Syariah Ditinjau Dari Planned Behaviour Theory (Survei Pada Masyarakat Kota Bekasi) - Sumaryo, Asep; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
Indonesia is a country with the largest Muslim population in the world of its 240 million people,88.2% are Muslims. Islamic banks exist because of the public's need for alternative transactions thatare interest-free. However, the growth of Islamic banks in Indonesia is still not optimal, one of thefactors is that people are still not enthusiastic about Islamic banks and the lack of intention of thepeople to become customers of Islamic banks. There are several factors that affect the intention interms of planned behavior theory, namely attitudes, subjective norms and perceptions of behaviorcontrol. So the research aims to determine the effect of attitudes, subjective norms and perceptionsof behavioral control on the intention of the people of Bekasi city to become customers in Islamicbanks. The research method uses multiple linear regression analysis. The data used are the results ofquestionnaires distributed to 12 districts in the city of Bekasi. The sample consisted of 132 people inBekasi city who were taken by using purposive sampling technique. Data were tested partially andsimultaneously. The data is processed using SPSS (Statistical Product and Service Solution) version22. The results of this study show partially that attitude variables have a positive and significant effect,subjective norm variables have a positive and significant effect, behavioral control perceptions have apositive but insignificant effect on intention to become a customer. Islamic Bank. Meanwhile, attitudes,subjective norms and perceived behavioral control simultaneously have a significant positive effect onthe intention to become a customer of Islamic banks. Future research is expected to expand the scopeof research, add variables and other factors and extend the research period.